The awareness and acceptance of the tourism brand “heart of the Hungarian Great Plain” and its attractions - Kóródi Márta; Mondok Anita; Szabó Attila („RIK-U” Kft., 2020)
Abstract. Beyond the successful economic, cultural, technological and ecological operation of an area, a competitive destination is able to attract travellers continuously and provide visitors with memorable experiences. Well-built image, communication and collaborations also significantly influence the competitive position. Although the slogan ‘Heart of the Great Plain’ used to identify the JászNagykun-Szolnok County of Hungary as a tourism destination, it meets all requirements generally specified, the perception of its success is closely linked to the awareness of the destination. The assessment of the detailed aspects afore will be presented by analysing the data of a large-sample (n=1037) research conducted among visitors of the destination during the summer of 2019. The conclusions show the need to exploit and develop the existing attractions innovatively by providing complex experience-generating tourism packages that attract a wide range of new travellers from different market segments.
https://kmf.uz.ua/wp-content/uploads/2020/09/final_2_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008123
Keywords: tourism destination management; brand management; experience management